INTRA- AND INTERPROVENANCE VARIATIONS IN LEAF MORPHOMETRIC TRAITS IN EUROPEAN BEECH (FAGUS SYLVATICA L.) - Stojnić, Srđan; Orlović, Saša; Miljković, Danijela; von Wuehlisch, Georg (Archives of Biological Sciences, 2016)
European beech (Fagus sylvatica L.) is one of the most important tree species in Europe. Due to substantial genetic diversity and phenotypic plasticity, beech has successfully adapted to different environments within its natural range. Provenance tests provide a good basis for studying within- and between-provenance genetic variation, due to homogeneous within-trial environmental conditions. The aim of the present study was to determine the within- and between-provenance genetic variability of certain leaf morphological traits among eleven beech provenances, grown in a common garden experiment. Univariate analysis of variance (ANOVA) was used to test for differences among the studied beech provenances. Principal component analysis (PCA) allowed a complex assessment of the relationships among the provenances and an estimation of multivariate relations among the analyzed characters. The results of the study revealed the existence of substantial variability among provenances (p<0.001). Likewise, high genetic variability was observed at the intra-provenance level (p<0.001). The first three principal components (PC1-PC3) explained approximately 81% of the total variance among the European beech provenances tested. The highest contribution on PC1 corresponded to variables related to leaf size: leaf area (-0.882) and leaf width (-0.876). Based on the position of provenances on a PCA scatter plot, it could be assumed that European beech is characterized by a more ecotypic pattern of genetic variation rather than by clinal variation. Also, the presence of considerable genetic diversity within provenances will be important in the light of climate change impact on beech, since it could potentially facilitate rapid adaptation. DOI: 10.2298/ABS151008064S Key words: European beech; provenance trial; leaf morphological traits; within- and between-provenance variation. Received: October 8, 2015; Revised: December 7, 2015; Accepted: January 19, 2016; Published online: July 28, 2016 How to cite this article: Stojnić S, Orlović S, Miljković D, von Wuehlisch G. Intra- and interprovenance variations in leaf morphometric traits in European beech (Fagus sylvatica L.). Arch Biol Sci. 2016;68(4):781-8.